Higher Mediterranean Diet Quality Scores and Lower Body Mass Index Are Associated with a Less-Oxidized Plasma Glutathione and Cysteine Redox Status in Adults. Issue 2 (27th February 2018) - Bettermann, Erika L; Hartman, Terryl J; Easley, Kirk A; Ferranti, Erin P; Jones, Dean P; Quyyumi, Arshed A; Vaccarino, Viola; Ziegler, Thomas R; Alvarez, Jessica A
Abstract: Background: Both systemic redox status and diet quality are associated with risk outcomes in chronic disease. It is not known, however, the extent to which diet quality influences plasma thiol/disulfide redox status. Objective: The purpose of this study was to investigate the influence of diet, as measured by diet quality scores and other dietary factors, on systemic thiol/disulfide redox status. Methods: We performed a cross-sectional study of 685 working men and women (ages ≥18 y) in Atlanta, GA. Diet was assessed by 3 diet quality scores: the Alternative Healthy Eating Index (AHEI), Dietary Approaches to Stop Hypertension (DASH), and the Mediterranean Diet Score (MDS). We measured concentrations of plasma glutathione (GSH), cysteine, their associated oxidized forms [glutathione disulfide (GSSG) and cystine (CySS), respectively], and their redox potentials (Eh GSSG and Eh CySS) to determine thiol/disulfide redox status. Linear regression modeling was performed to assess relations between diet and plasma redox after adjustment for age, body mass index (BMI), sex, race, and history of chronic disease. Results: MDS was positively associated with plasma GSH (β = 0.02; 95% CI: 0.003, 0.03) and total GSH (GSH + GSSG) (β = 0.02; 95% CI: 0.003, 0.03), and inversely associated with the CySS:GSH ratio (β = –0.02; 95% CI: –0.04, –0.004). There were significant independent associations between individual MDS components (dairy, vegetables, fish, and monounsaturated fat intake) and varying plasma redox indexes ( P < 0.05). AHEI and DASH diet quality indexes and other diet factors of interest were not significantly correlated with plasma thiol and disulfide redox measures. Conclusion: Adherence to the Mediterranean diet was significantly associated with a favorable plasma thiol/disulfide redox profile, independent of BMI, in a generally healthy working adult population. Although longitudinal studies are warranted, these findings contribute to the feasibility of targeting a Mediterranean diet to improve plasma redox status.